Is there a role for early chemotherapy in the management of pituitary adenomas? - Lin, Andrew L. (Neuro Oncol, 2016)
Pituitary adenomas are benign intracranial neoplasms that are frequently well-controlled with standard treatments that include surgical resection, radiotherapy, and agents that modulate hormonal excess. Unfortunately, a subset of patients remains uncontrolled or develops complications from these interventions. For these patients, chemotherapy is an additional treatment option that could improve outcomes. Temozolomide is an oral chemotherapy with a favorable side-effect profile that has shown activity against pituitary adenomas. Its non-overlapping toxicity and ability to induce rapid tumor regression renders it a potentially important adjunctive treatment. In patients with tumors that cannot be optimally addressed with standard treatments, there may be a role for early initiation of temozolomide.